ELASTICITY RESPONSE BY COMMUTER AS PRIVATE VEHICLE USERS TO CHANGES OF PARKING PRICING STRATEGY CASE STUDY: BANDUNG URBAN AREA - Nur'Afalia, Dian
Parking pricing is one of the most effective tools in influencing driver behavior patterns, so urban planners and policy makers can use this policy to regulate the amount of trips in the city center. There is parking pricing strategy also in Bandung’s plan. Bandung as an urban area which is the center of Metropolitan Bandung Raya dan centre of various activities causes high movement generation. The high movement generation especially the movement by commuters. The centre area of Bandung with the various activity and density has a significant traffic problem. The massive movement using private vehicle and the using on-street parking causes congestion in Bandung Urban Area. The using of on-street parking causes the increasing of road capacity. Eventhough, 70% of area served by off-street parking lots. Parking tariff are relativly cheap base on 88,5% respondent might be one the reason the using of private vehichle to centre of Bandung Area.. And also, It is important to understand how users in a centre of the city respond to a parking pricing new policy. In this research, the various density in centre area represented by build enviroment based on 5Ds aspects. Base on logit binary analysis, there is relation between compact-congestion, not compact-congestion and not compact-not congestion with the changes of parking pricing and commuters behaviour. To support these hypotheses, this study employed four binary logistic models base on the hoghest response precentage. The relation with the hihest neglekerke R square test as follow : P/1-P = 3,519 + 1,905 (X1.3) + 1,976 (X1.4) + 1,585 (X1.5) – 0,001 (X.2). From the model, we can conclude that there is a relation between parking pricing, built enviroment and commuters behaviour. Then, understand how commuters in a centre of the city respond to a parking pricing new policy. Based on elasticity analysis originated from stated preference questionnaires distributed to 200 respondents. It turns out that the responses given by commuters of on-street parking in the six categories have a fairly uniform tariff range, that is in the range of IDR 2500 to IDR 7500 per hour. But IDR 5500 which turns out to be considered as the most effective parking rates, wherein the elasticity of private vehicle users who still choose to park at exsisting locations is in the range of -1,43 to -8,78. While in the range of 2,17 to 5,04 that shifting to public transportation. And in the range of 1,72 to 3,51 that move to another parking area.